Comparative study on secondary metabolites from different citrus varieties in the production area of Zhejiang - Lin, Mei; Xu, Chengnan; Gao, Xueying; Zhang, Weiqing; Yao, Zhoulin; Wang, Tianyu; Feng, Xianju; Wang, Yue (Frontiers in Nutrition, 2023)
To investigate the distribution pattern of bioactive components and their correlations between citrus varieties, we thoroughly analyzed secondary metabolites (including flavonoids, phenolic acids, carotenoids and limonoids) in the peel and pulp of 11 citrus varieties from the production area of Zhejiang. Citrus peels accumulated far more above metabolites than in the pulp, and the accumulation varied significantly between species. Flavonoids were the most abundant compounds, followed by phenolic acids, with carotenoids and limonoids were far less abundant than the first two, but limonoids were greater than carotenoids. Hesperidin was the main flavonoids in most varieties, but in Cocktail Grapefruit and Changshanhuyou were naringin, with Ponkan contained most abundant of polymethoxylatedflavones (PMFs). The major components of phenolic acids, carotenoids and limonoids were ferulic acid, β-cryptoxanthin and limonin, respectively. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) indicated that these components were mostly correlated with each other, and these citrus varieties could be categorized into four groups by pulp and three groups by peel. The obtained results filled the data gap of secondary metabolites from local citrus, furtherly, could provide data references for citrus resource utilization, selection and breeding of superior varieties and other research.